Islamic Religious Education Curriculum as a Vessel for Developing Islamic Character in the Modern Era - Muhammad Aldi; Juliani; Nazwa Intani; Pingkan Nabila; Sutia Nur Aulia Liza (Journal of Contemporary Islamic Primary Education, 2024)
Islamic Religious Education (PAI) plays a vital role in shaping the Islamic character of students in the modern era. The PAI curriculum is designed to instill Islamic values that are relevant to contemporary challenges, helping to shape individuals with noble morals and integrity. This article discusses the implementation of the PAI curriculum in character building, the methods used, and the challenges faced in the context of modernization.